The teeny-weeny unicorn's great big wish [book with audioplayer] - Harris, Shawn (Artist); Butler, Ron, Jr ([Library Ideas, LLC], 2025)
A tiny unicorn longing to be big takes one last chance to make his wish come true, and with a gust of lucky wind and a fairy princess, discovers an unexpected surprise.